Evaluation of a photographic method to measure dental angulation - Amorim,Jordana Rodrigues (2014)
Objective: To analyze the reliability and reproducibility of a simplified method for analysis of dental angulation using digital photos of plaster dental casts. Methods: Digital and standardized photographs of plaster casts were performed and posteriorly imported to an angle reading graphic program in order to have measurements obtained. Such procedures were repeated to evaluate the random error and to analyze reproducibility through intraclass correlation. The sample consisted of 12 individuals (six male and six female) with full permanent dentition orthodontically untreated. The analyses were bilaterally carried out, and generated 24 measurements. Results: The random error showed variation of 0.77 to 2.55 degrees for teeth angulation. The statistical analysis revealed that the method presents excellent reproducibility (p < 0.0001) for all teeth, except for the upper premolars. In spite of that, it is still considered statistically significant (p < 0.001). Conclusion: The proposed method presents enough reliability that justifies its use in the development of scientific research as well as in clinical practice.